Family‐based Intervention for Legal System‐involved Girls: A Mixed Methods Evaluation. Issue 1 (5th November 2020) - Anderson, Valerie R.; Rubino, Laura L.; McKenna, Nicole C.
Abstract: The increased proportion of juvenile court‐involved girls has spurred interest to implement and evaluate services to reduce girls' system involvement. The purpose of this study was to examine the effectiveness of a family‐based intervention by using a dominant sequential mixed methods evaluation approach. First, we examined quantitative data using a quasi‐experimental design to determine whether the family‐based intervention reduced recidivism among court‐involved girls. Propensity score matching (PSM) was used to construct statistically equivalent groups to compare one‐year recidivism outcomes for girls who received the court‐run family‐based intervention ( n = 181) to a group of girls on probation who did not receive the intervention ( n = 803). Qualitative interviews ( n = 39) were conducted to contextualize the quantitative findings and highlighted the circumstances that family‐focused interventions for court‐involved girls. Girls who received the program had slightly lower recidivism rates following the intervention. The qualitative findings contextualized the quasi‐experimental results by providing an explanation as to the girls' family circumstances and insights into the mechanisms of the intervention. Results highlighted the importance of family‐focused interventions for juvenile justice‐involved girls. These findings have practical and policy implications for the use interventions—beyond the individual level—with adjudicated girls and offer suggestions for ways to improve their effectiveness using a community psychology lens. In addition, this paper includes a discussion of evaluating of juvenile court programming from a community psychology perspective including strengths, challenges, and considerations for future work in this area. Highlights: There is limited research on the effectiveness of interventions for legal system‐involved girls. Quantitative data revealed girls who received the family intervention had slightly lower recidivism. Qualitative results contextualized the family environment and intervention mechanisms. Moving forward it is important to develop legal interventions that move beyond the individual‐level.